Relativism and reality : a contemporary introduction - Kirk, Robert, 1933- (Routledge, 1999)
Relativism and Reality: A Contemporary Introduction examines the philosophical tradition surrounding the question of reality and relativism, the belief that reality somehow depends on what we think.